Study of the Characteristics of Cellular Lightweight Concrete (CLC) Bricks Using (Palm Kernel Shell) Ash as a Comment Additive - Naldi, Septri; Setiawan, Beny; Kumala Sari, Resy (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Riau Province is one of Indonesia’s largest palm oil–producing regions, generating substantial biomass waste such as palm kernel shells. One potential use of this waste is Palm Kernel Shell Ash (PKS-Ash), which contains silica (SiO₂) and alumina (Al₂O₃) that are beneficial for cementitious reactions. This study aims to evaluate the effect of PKS-Ash as a cement additive on the properties of Cellular Lightweight Concrete (CLC) bricks, particularly unit weight, water absorption, and compressive strength. A laboratory-scale experimental method was applied. The test specimens were produced using cement, sand, water, a foaming agent, and PKS-Ash with variations of 0%, 4%, 6%, and 8% by weight of cement. All specimens were tested at curing ages of 7, 14, 21, and 28 days in accordance with SNI 8640-2018. The results at 28 days showed that the addition of PKS-Ash significantly influenced the characteristics of the CLC bricks. Compressive strength increased with higher PKS-Ash content, reaching a maximum value of 1.775 MPa at the 8% variation, compared to 0.975 MPa for the control mixture. The unit weight of the specimens ranged from 1,304.29 kg/m³ to 1,716.44 kg/m³. Water absorption values varied, with the lowest absorption observed in the 0% mixture and the highest in the 4% mixture. The study concludes that PKS-Ash has strong potential as a sustainable additive to improve the compressive strength of CLC lightweight bricks while promoting effective utilization of palm oil industry waste.